PERAWATAN GINGIVOSTOMATITIS HERPETIKA PRIMER PADA PASIEN REMAJA - Ganesha, Raziv (Interdental: Jurnal Kedokteran Gigi, 2020)
Introduction: Primary Herpetic Gingivostomatitis (PHGS) is a primary infection to Herpes Simplex Virus type 1 (HSV-1). PHGS often occurs in pre-school-aged children, but also occur in school-age children and teenager. This case report purpose to discuss management of PHGS in teenager. Case: Patient a 12-year-old with chief complaints are many ulcers in mouth. Ulcer appears after the patient has a fever for 2 days. The patient has never experienced like this before. On Intra Oral examination found multiple ulcers, varying in size, pain in the upper labial, lower labial, lower gingival and lower mucobucalfold. Case Management: patient was given a complete blood count and IgG antigen HSV-1, with reactive results. Patients received treatment in the form of aloe vera extract gel, Immunomodulator syrup. ulcers healed after 12 days of treatment. Conclucion: PHGS is a case that often occurs in pre-school age but also occur in school-age children and teenager. Anamnesis, objective examination and supporting examinations is needed to diagnosis to choose proper therapy.